2009
DOI: 10.1111/j.1440-1746.2008.05693.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated adiponectin serum levels in patients with chronic alcohol abuse rapidly decline during alcohol withdrawal

Abstract: Alcohol exhibits a specific effect on SAL that is dose and time dependent, and correlates with the degree of hepatic damage. Alcohol does not seem to affect adiponectin expression directly in adipocytes but potentially via mediators systemically released as a result of the chronic alcohol intake.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
23
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 37 publications
(28 citation statements)
references
References 31 publications
4
23
0
1
Order By: Relevance
“…ARL15 was previously shown to be associated with adiponectin levels, but the exact function of this gene is still unknown (Richards et al, 2009). Several studies have found that adiponectin levels are elevated in patients with chronic alcohol abuse (Buechler et al, 2009) and might also be associated with alcohol craving (Hillemacher et al, 2009). The enrichment analysis using HaploReg showed that SNPs identified at this locus in the COGA dataset predicted significant (p < 5.2 × 10 −4 ) enrichment of enhancers in H1 and leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…ARL15 was previously shown to be associated with adiponectin levels, but the exact function of this gene is still unknown (Richards et al, 2009). Several studies have found that adiponectin levels are elevated in patients with chronic alcohol abuse (Buechler et al, 2009) and might also be associated with alcohol craving (Hillemacher et al, 2009). The enrichment analysis using HaploReg showed that SNPs identified at this locus in the COGA dataset predicted significant (p < 5.2 × 10 −4 ) enrichment of enhancers in H1 and leukemia cell lines.…”
Section: Discussionmentioning
confidence: 99%
“…Several reports have shown that ethanol feeding reduces the plasma adiponectin level in mice, rats, or micropigs (36,43,48). In contrast, some studies demonstrated that ethanol exposure increases the plasma adiponectin level in mice or patients with alcoholic hepatitis (5,11,44). Despite the controversial results, administration mouse recombinant adiponectin has been shown to attenuate alcohol-induced steatosis and inflammation (43).…”
Section: G554 Rosiglitazone Reverses Ethanol-induced Adipose Dysfunctionmentioning
confidence: 95%
“…While MCD diet alone preferentially causes bile duct injury and cholestasis, ethanol interferes with protective antioxidative pathways, and subsequently combination of MCD diet and ethanol aggerates liver injury [88]. In humans chronic alcohol abuse is even associated with higher circulating levels of the hepatoprotective adipokine adiponectin which is significantly reduced in obesity and NAFLD [25,89]. Moderate alcohol intake has been shown to exert protective effects by increasing systemic high density lipoprotein thereby lowering inflammation and stimulating reverse cholesterol transport.…”
Section: Alcohol and Alcohol Metabolizing Enzymesmentioning
confidence: 98%